A de novo Loss-of-function Variant in RAPGEF6 Supports its Role in Neuropsychiatric Disorders - Simone Treccarichi; Mirella Vinci; Maria Grazia Figura; Antonino Musumeci; Miriam Virgillito; Carla Papa; Valeria Chiavetta; Desiree Brancato; Francesca Bruno; Concetta Federico; Justin Simo; Roberta La Piana; et al. (Journal of Molecular Neuroscience, 2026)
RAPGEF6 is a member of the guanine nucleotide exchange factor (GEF) subfamily that acts on Rap small GTPases and contains a Ras/Rap-associating domain. Although deficiency of this gene has previously been linked to schizophrenia, no MIM phenotype entry currently associates RAPGEF6 with a defined clinical condition. In this study, trio-based whole-exome sequencing (WES) was performed in an individual presenting with psychiatric disorders and mild intellectual disability. WES revealed a de novo frameshift variant, c.272dup (p.Pro92Serfs*6), in the RAPGEF6 gene (NM_016340.6). This variant was classified as likely pathogenic according to ACMG criteria. Nonetheless, the contribution of additional genetic factors not detected by WES cannot be excluded. According to developmental transcriptomic data from the BrainSpan database, RAPGEF6 is expressed in the human brain across the entire lifespan and participates in neuron projection development, Rap-protein signal transduction, and regulation of GTPase activity. Structural variation data from DECIPHER further indicate that copy-number variants involving RAPGEF6 are primarily associated with intellectual disability and micrognathia. In addition, DECIPHER shows that RAPGEF6 is highly intolerant to loss-of-function (LoF) variants. Both NMD-Esc predictor and Mutation Taster suggest that the identified frameshift mutation is likely to trigger nonsense-mediated decay (NMD) of the RAPGEF6 transcript, resulting in loss of protein production. In addition, RAPGEF6 expression progressively increased during retinoic acid-induced neuronal differentiation of SK-N-BE neuroblastoma cells, supporting a potential role of this gene in neuronal maturation processes. Together, these data support a contributory role of RAPGEF6 haploinsufficiency in neurodevelopmental and psychiatric phenotypes, reinforcing its emerging relevance in neuropsychiatric disorders.

Influence of red gorgonian (Paramuricea clavata) forests on coralligenous community structure across different regions, seasons, thermal environment, and water trophic state - La Manna Gabriella; Bolinesi Francesco; Bosch-Belmar Maria del Mar; Colletti Alberto; Di Marino Claudio; Fabietti Ylenia; Fraschetti Simonetta; Licciardi Luca; Mancuso Francesco Paolo; Mangoni Olga; Morello Giuseppe; Musumeci Simone Maria Santo; et al. (Coral Reefs, 2026)

Occurrence of Phyllariopsis brevipes (C. Agardh) E.C. Henry & G.R. South 1987 in the Gulf of Naples - Alberto Colletti; Antonia Chiarore; Sara De Benedictis; Erika Fabbrizzi; Giulio Franzitta; Luca Licciardi; Simone Musumeci; João Neiva; Chiara Silvestrini; Simonetta Fraschetti (Marine Ecology, 2024)
The first record of the kelp species Phyllariopsis brevipes in the Campania Region (Tyrrhenian Sea, South Italy) is here reported. The species has been observed in October 2021 in four sites along Sorrento Peninsula and Capri Island coast during scuba diving surveys. P. brevipes grew on living thalli of crustose coralline algae from 32 up to 55 m depth, occasionally forming dense aggregations with a maximum cover of about 0.2 m 2 . The DNA barcoding analysis on the basis of the cox1 gene supported the identification, with 98.36% of similarity between the sample collected in this study (NCBI accession number: PP622796 ) and a sequence obtained from a specimen from Provence, Mediterranean France (NCBI accession number: GQ368264 ). The study area can be considered a stepping stone for the species dispersion. The occurrence of P. brevipes can be related to upwelling and good water quality and the monitoring of its health status might be a sentinel of environmental changes.